Effects of a 6-Week Bench Press Program Using the Freak Bar in a Sample of Collegiate Club Powerlifters. Issue 4 (April 2018) - Ghigiarelli, Jamie J.; Pelton, Luke M.; Gonzalez, Adam M.; Fulop, Andras M.; Gee, Joshua Y.; Sell, Katie M.
Abstract : Abstract: Ghigiarelli, JJ, Pelton, LM, Gonzalez, AM, Fulop, AM, Gee, JY, and Sell, KM. Effects of a 6-week bench press program using the freak bar in a sample of collegiate club powerlifters. J Strength Cond Res 32(4): 938–949, 2018—Powerlifters train using specialty bars for unstable load (UL) training. For the bench press, the acute effects of UL are mixed, with few studies that examine training interventions. The purpose of this study was to examine the effects of a 6-week bench press training program that uses the Freak Bar (FB) as compared to a traditional barbell (TB) on maximum bench press, peak force, and peak impulse. Seven men and 3 women (21 ± 2.0 years, 172.2 ± 2.9 cm, and 95.3 ± 20.3 kg) were required to bench press 2 days per week as part of a structured program. On the second bench press day, the FB and TB groups performed 3-position pause bench presses at 60–70% one repetition maximum (1RM). One repetition maximum, peak force, and peak impulse were measured before test and after test after the 6-week program. Peak force and peak impulse were tested at 3 bench positions, including the presticking, sticking, and poststicking points, defined by the distance of the barbell from the chest. Posttraining 1RM for the FB group and TB group increased 6.7% (6.78 ± 1.6 kg, p = 0.006) and 4.3% (4.5 ± 2.7 kg, p = 0.23), respectively, with no significant differences between the groups ( p = 0.589, η p 2 = 0.044). There were no significant differences between the groups at each bench position for peak force ( p = 0.606) or peak impulse ( p = 0.542). Freak Bar can be an alternative for improving maximum strength and peak force but is not significantly better than TB training when performing the 3-position pause bench press.